TAX AVOIDANCE & CORPORATE RISK: MODERATION BY EXECUTIVE CHARACTERISTICS AND GENDER DIVERSITY - Verani Carolina; Endah Purnama Sari Eddy (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study examines the effect of tax avoidance on corporate risk. Next, the moderating effect of executive characteristics and gender diversity is investigated in this association. The study examined Indonesia’s nonfinancial listed companies, collecting a sample of 265 observations during 2020-2024. Hypotheses were tested using moderated regression with panel data. It was found that companies that avoid taxes aggressively have a higher level of corporate risk. The presence of risk-averse executive characteristics and women weakens the effect of tax avoidance on corporate risk. This research contributes by providing the latest references regarding Indonesian tax avoidance behavior that poses risks to companies and encouraging companies in Indonesia to be aware of the importance of executive characteristics and gender diversity.